2018
DOI: 10.1038/s41598-018-30445-2
|View full text |Cite
|
Sign up to set email alerts
|

Resting-state alpha power is selectively associated with autistic traits reflecting behavioral rigidity

Abstract: Previous research suggests that variation in at-rest neural activity correlates with specific domains of the ASD phenotype; however, few studies have linked patterns of brain activity with autistic trait expression in typically developing populations. The purpose of this study was to examine associations between resting-state electroencephalography (EEG) and three domains of the broader autism phenotype (social interest, rigidity, and pragmatic language) in typically developing individuals. High-density scalp … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 30 publications
3
15
0
Order By: Relevance
“…The impedance of all channels, excluding the outermost part, was maintained below 30 kΩ throughout the experiment to standardize the EEG recordings (Ferree et al, 2001). This impedance standard was consistent with other studies using the same EEG system (Carter Leno et al, 2018b, 2018a; Robertson et al, 2019).…”
Section: Methodssupporting
confidence: 92%
“…The impedance of all channels, excluding the outermost part, was maintained below 30 kΩ throughout the experiment to standardize the EEG recordings (Ferree et al, 2001). This impedance standard was consistent with other studies using the same EEG system (Carter Leno et al, 2018b, 2018a; Robertson et al, 2019).…”
Section: Methodssupporting
confidence: 92%
“…However, contrasting data reveal that resting-state parietal alpha power has a positive association with some traits characteristic of the cognitive rigidity, that is, the difficulty to adapt to changes and the tendency towards repetitive behaviors (evaluated with Broad Autism Phenotype Questionnaire—BAP-Q— p < 0.05) found in autism, suggesting that the broader autism phenotype could be associated with different EEG patterns [ 52 ].…”
Section: Electroencephalographic Patternsmentioning
confidence: 99%
“…We predicted that variation in social context would alter resting-state oscillatory brain activity. Specifically, we expected that alpha would be sensitive to changing social dynamics based on the well-established evidence that alpha indexes vigilance and arousal, as well as prior work demonstrating an association between alpha activity and autistic traits (11). Additionally, we expected that variation in oscillatory activity between contexts, as a marker of sensitivity to social context, would be associated with social cognition, as measured through self-report of social ability.…”
Section: Introductionmentioning
confidence: 99%
“…Neuroimaging studies consistently implicate atypical resting activity across multiple modalities in clinical populations with impaired social cognition (7)(8)(9)(10). Even in nonclinically ascertained populations, EEG studies have identified alterations in power in the alpha frequency range (8)(9)(10)(11)(12)(13) associated with social cognition (11). Despite strong evidence for an association between at-rest brain activity and social function, the majority of research has measured brain activity when participants are in isolation in an EEG recording chamber, MRI, or MEG; we know little about brain activity during in vivo social interactions.…”
Section: Introductionmentioning
confidence: 99%